Surgical treatment of acute patellar dislocation associated with bony avulsion in children: Kirurško zdravljenje akutnega izpaha pogačice s kostnim odlomkom pri otrocih - Fokter, Samo K.; Dovnik, Andraž; Fokter Dovnik, Nina (Acta Medico-Biotechnica, 2021)
Purpose: The management of acute patellar dislocation in children and adolescents is controversial. Traditionally, most first–time traumatic patellar dislocations have been treated nonoperatively. However, due to new knowledge about medial patellar stabilizers some authors have advocated for surgical repair. The present report describes the mid–term subjective and functional results of operative treatment of acute patellar dislocation in children less than eighteen years of age with concomitant osteochondral fracture.Methods: Data on a cohort of sixteen patients (eight girls and eight boys) aged 14.9 years (mean, range 12–17 years) with acute patellar dislocation were retrospectively collected. Intraarticular fragments were detected in all patients in conventional radiographs. Operative treatment consisted of arthroscopic removal (12 cases) or refixation (4 cases) of the osteochondral fragments and direct repair of the damaged medial patellofemoral ligament (MPFL) if that was still feasible (13 cases). All patients were seen at six months, and a telephone interview with twelve patients (75%) was conducted at four years (mean, range 2–7 years).Results: Of the sixteen patients, two (12.5%) had a recurrent patellar luxation. The subjective IKDC score at the time of the most recent follow–up was 86 (mean, range 63–100), and the Marx Activity Rating Scale score was 9.2 (mean, range 2–16).Conclusions: Direct surgical repair of the injured MPFL may be considered an option to prevent subsequent dislocation and subluxation in first–time traumatic dislocation of the patella in children and adolescents with osteochondral fractures and substantial disruption of medial patellar stabilizers.
Keywords: acute patellar dislocation; patellofemoral bony avulsion; dislocation in children; pediatric injury; surgical treatment